Oral expression in children and tales - Martínez Chepe, Adriana Carolina (2015)
This article is intended for promoting children’s improvement in one of their primordial needs such as language development through an Educational program. It consists in the technique of storytelling to progress the oral expression in children. It proposes to develop a richer vocabulary, a clearer and coherent pronunciation and understanding of messages. In this way, they can express ideas fluidly and participate in dialogues with their peers and with adult actively. They also make conjectures and give their opinions, relate experiences, explain inferences, judge the attitudes of the characters of the text and distinguish between real or fictional events; through storytelling. Moreover, this article also achieves to make a reflection about the teacher’s performance.